Content Creation Teams In Strengthening Students’ Digital Literacy At Fadlun Minalloh Islamic Boarding School - Muhammad Nur Aziz Saputra; Karwadi (Sunan Kalijaga International Journal on Islamic Educational Research, 2026)
The development of digital technology has transformed the way educational institutions, including Islamic boarding schools, build communication, disseminate information, and develop students’ literacy skills. In this context, the Islamic boarding school content creation team functions not only as a media publication manager but also as a facilitator of digital literacy learning. This study aims to analyze the role of content creators at the Fadlun Minalloh Islamic Boarding School in Bantul in strengthening students’ social media information literacy, identifying literacy practices that emerge from students’ involvement in media activities, and explaining factors that support and hinder their implementation. This study used qualitative field research with data collection techniques through semi-structured interviews, observation, and documentation. The informants consisted of two students, two media team members, one ustaz, and one media division leader selected through purposive sampling. The data were analyzed thematically, while validity was strengthened through source and technique triangulation. The findings show that the content creation team functions as a mediator of religious values and social media information literacy through regulated access, message comprehension, content evaluation, guided content production, and ethical interaction. The media team also strengthens value-based digital literacy by linking digital communication with discipline, worship, daʿwa, and pesantren identity. Supporting factors include leadership support, facilities, team enthusiasm, alumni networks, and WhatsApp-based circulation. Inhibiting factors include unstable production discipline, coordination problems, and technical limitations. This study confirms that pesantren-based media teams can become practice-based literacy spaces, although the findings should be understood within the context of a single-site qualitative study.